The Colonial Legacy in France : Fracture, Rupture, and Apartheid - Pernsteiner, Alexis; Thomas, Dominic Richard David; Blanchard, Pascal; Bancel, Nicolas (Book collections on Project MUSE., 2017)
"Debates about the legacy of colonialism in France are not new, but they have taken on new urgency in the wake of recent terrorist attacks. Responding to acts of religious and racial violence in 2005, 2010, and 2015 and beyond, the essays in this volume pit French ideals against government-sponsored revisionist decrees that have exacerbated tensions, complicated the process of establishing and recording national memory, and triggered divisive debates on what it means to identify as French. As they document the checkered legacy of French colonialism, the contributors raise questions about France and the contemporary role of Islam, the banlieues, immigration, race, history, pedagogy, and the future of the Republic. This innovative volume reconsiders the cultural, economic, political, and social realities facing global French citizens today and includes contributions by Achille Mbembe, Benjamin Stora, Françoise Verges, Alec Hargreaves, Elsa Dorlin, and Alain Mabanckou, among others"--Provided by publisher.